Resveratrol Sebagai Adjunctive Therapy Pasien Periodontitis dengan Diabetes Melitus - Christin Maitimu, Fergy; Harini Endah Meidianti, Dwi; Syifa Naufal, Nafia; Nabillah Rulifa, Syarah (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Background: Periodontitis is one of the most common chronic inflammatory diseases in the world, affecting oral health. Chronic periodontitis is considered a common complication of Diabetes Mellitus (DM), establishing a bidirectional relationship between periodontitis and DM. Resveratrol is a polyphenolic stilbene found in red wine, grape skins, mulberries, and peanuts. Resveratrol exhibits a variety of beneficial properties such as anti-carcinogenic, anti-platelet aggregation, anti-allergic, antioxidant, and anti-inflammatory agents. Objectives: The aim of this study is to investigate the effect of resveratrol as an adjunct therapy for periodontitis in patients with Type 2 Diabetes Mellitus. Methods: This literature review utilizes an electronic database search method, specifically Google Scholar. The keywords used are “Resveratrol in periodontitis” and “Resveratrol for type 2 Diabetes Mellitus.” The inclusion criteria consist of journals published between 2016 and 2024 with research designs being randomized clinical trials or clinical trials on humans. Results: The results obtained from this literature review indicate that resveratrol is effective as an adjunct therapy for periodontitis in patients with Type 2 Diabetes Mellitus as it can reduce plaque index, bleeding index, gingival index, clinical attachment loss, probing depth, IL-1B, IL-6, and insulin resistance. Conclusion: The implementation of resveratrol as an adjunct therapy can improve periodontal and metabolic health in patients with Type 2 Diabetes Mellitus..